The Lack of Love and Iron, The two causes of Alzheimer's - Joan Manuel Rodriguez Nunez (Annals of Alzheimer's and Dementia Care - Peertechz Publications, 2019)
Objective: By the lack of initiative by force (Faith) Iron man lives. Iron defi ciency causes anemia, anemia causes dementia, Alzheimer dementia and Alzheimer's produces cognitive impairment in memory produces bases. Well hear him. The Iron Will Alkaline, the answer is yes. Methodology: On the basis of Love and the use of Iron and its allies, which are the B vitamins, Vitamin C, E and vitamin A. It is necessary to remember that there is to try to fi ght the greatest sustenance Anemia in all its contrarestantes.